2009
DOI: 10.1017/s0022029909990422
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of increased milking frequency as an additional treatment for cows with clinical mastitis

Abstract: This field study focused on the possible effects of increased milking frequency (milking four times a day in comparison with milking twice a day) on clinical and bacteriological cure rates of clinical, antibiotically treated mastitis cases. Parameters tested were clinical, microbiological and full (cytomicrobiological) cure as well as the development of milk yield after the clinical mastitis episode. Cows from a large dairy herd meeting the study criteria (n=93) were assigned to two treatment groups by a syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 7 publications
3
7
0
2
Order By: Relevance
“…Frequent milking is a traditional treatment for mastitis and is commonly recommended as a supportive treatment for clinical mastitis (Radostits et al ., ). A field study on its efficacy in treating clinical mastitis failed to show any beneficial effects, however (Krömker et al ., ). Similar results were published for an experimental study using an E. coli mastitis model (Leininger et al ., ).…”
Section: Characteristics Of Escherichia Coli Mastitismentioning
confidence: 97%
“…Frequent milking is a traditional treatment for mastitis and is commonly recommended as a supportive treatment for clinical mastitis (Radostits et al ., ). A field study on its efficacy in treating clinical mastitis failed to show any beneficial effects, however (Krömker et al ., ). Similar results were published for an experimental study using an E. coli mastitis model (Leininger et al ., ).…”
Section: Characteristics Of Escherichia Coli Mastitismentioning
confidence: 97%
“…8 A more recent study reported that milking 4 times as a supportive therapy for mild, moderate, and severe antimicrobially treated mastitis cases cannot be recommended. 64 A review of the history and studies regarding the efficacy of FMO for clinical mastitis is available. 65 The only study, to date, that reported improved efficacy with FMO indicated that use of frequent milking significantly improved clinical cure for naturally occurring acute E coli mastitis on day 2.…”
Section: Frequent Milk-outmentioning
confidence: 99%
“…36 In the present study, a high rate of culture-negative mastitis cases was found, which compares well with study results of Krömker and others. 43 In approximately 10-40 per cent of samples, pathogens are not identiied in routine clinical culture assays. [44][45][46] Culture-negative cases cannot be detected from a change in milk appearance or from clinical symptoms.…”
Section: Efectiveness Of Treatmentmentioning
confidence: 99%